(untitled) (Fiep Bulletin - online, 2014)
Introduction: Pilates method uses in an intense way the respiration, and therefore can alter respiratory muscles strength. Objective: to evaluate the benefits that the Pilates method promotes in respiratory function. Methodology: It treats of a study of a semi experimental type with quantitative approaching. The sample was of 46 young adults, with ages from 18 to 30 years, of both sexes. It was carried out a height, weight, respiratory muscle strength, current volume, minute volume and slow vital capacity verification. Two groups were formed: eutrophic and overweight/obesity. Results: After the stretching were observed significant results in Pimax (p<0,001) and Pemax (p<0,001) in both groups: in the current volume (p=0,02), minute volume (p=0,004) and vital capacity (p<0,001) in the eutrophic group and only in vital capacity in the overweight/obesity group. (p<0,001). Conclusion: Pilates method can be considered an extra tool by health professionals in the therapeutic aspect and might be tested by the person with a pneumopathy.